Textbook Characteristics That Support or Thwart Comprehension: The Current State of Social Studies Texts. Issue 3 (3rd May 2016) - Berkeley, Sheri; King-Sears, Margaret E.; Vilbas, Jessica; Conklin, Sarah
Abstract : Textbooks are heavily used in secondary-level content area classes, but previous research has identified numerous challenges for students associated with reading and understanding these texts. While students can learn reading strategies that help them better understand text, it is unclear the extent to which textbooks are written to promote or hinder the use of those strategies. The current study systematically coded and analyzed characteristics of current editions of middle school social studies textbooks from four major textbook publishers (N = 14). Findings suggest that there continue to be limitations inherent to textbooks that have the potential to "thwart comprehension, " and supplemental instruction will be required in order for students to learn. However, findings also reveal that contemporary textbooks contain features that "support comprehension, " which teachers may utilize to assist students with comprehension rather than augmenting with separate instructional materials. Implications for instruction, student learning, and textbook adoption are discussed.